Patrician landscapes and the picturesque in Nottinghamshire c.1750-c.1850 - Gaunt, Richard A. (Cambridge University Press, 2015)
This article considers the Dukeries estates of north Nottinghamshire in the hey-day of aristocratic power and prestige, from the mid-Georgian to the mid-Victorian period. It poses a contrast between visitors’ impressions of the area as one of constancy and continuity, a point of reassurance in an age of political and social upheaval, and the reality of internal changes from within. Closely crowded as these estates were, their aristocratic owners competed with one another to fashion the most economically viable and aesthetically pleasing symbol of status and power. The article pays close attention to the hold which picturesque principles exercised on individual owners and considers the role of plantation, animals and water in parkland management and improvement. Finally, the article considers the extent to which the estates were sites of contestation; owners attempted to keep unwanted plebeian incursions at bay, whilst carefully controlling access on set-piece occasions such as coming-of-age festivities.